2020
DOI: 10.1101/2020.08.21.20179416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of population density on the Covid-19 infected and mortality rates in India

Abstract: The residents living in areas with high population density, such as big or metropolitan cities have higher probability to come into close contact with others and consequently any contagious disease are expected to spread rapidly in dense areas. However, recently after analyzing Covid-19 cases in US researchers at the Johns Hopkins Bloomberg School of Public Health, London school of economics and IZA Institute of Labor Economics conclude that spread of Covid-19 is not linked with population density. Here we i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…In a study performed by Kadi and Khelfaoui in Algeria, the authors found that population density indeed played a role in the transmission of the virus [ 51 ]. This is also supported by a study done by Bhadra et al in different districts of India [ 26 ]. However, it cannot be a strong explanatory factor as to why the number of cases are as known [ 52 ].…”
Section: Resultssupporting
confidence: 80%
“…In a study performed by Kadi and Khelfaoui in Algeria, the authors found that population density indeed played a role in the transmission of the virus [ 51 ]. This is also supported by a study done by Bhadra et al in different districts of India [ 26 ]. However, it cannot be a strong explanatory factor as to why the number of cases are as known [ 52 ].…”
Section: Resultssupporting
confidence: 80%
“…demanding parameters such as human mobility and hygiene need to be taken into consideration for COVID-19 spread. The possible connection between population density and COVID-19 spread are demonstrated in the previous studies, which reported a possible linkage between higher population density and surge in COVID-19 cases (Bhadra et al, 2020;Coskun et al, 2021). Interestingly, in India the COVID-19 epicenters coincide with the emission hotspots and regions with higher population densities i.e.…”
Section: Co2 Emission Global Warming and Climate Changementioning
confidence: 75%
“…D_PERM was also analyzed as this might indicate that as many people die from the virus, the possibility of being infected of the other people is increased. PD , AGE and GDP_PERC were also included since it was found that these variables significantly affects the transmission of the virus as far as the social distancing and level of activity of people and their age is a concern [ 41 , 42 ]. RUPOP was computed as 1 minus the percentage of the urban population of the country.…”
Section: Methodsmentioning
confidence: 99%